Convective transport and scavenging of peroxides by thunderstorms observed over the central U.S. during DC3. Issue 8 (29th April 2016) - Barth, M. C.; Bela, M. M.; Fried, A.; Wennberg, P. O.; Crounse, J. D.; St. Clair, J. M.; Blake, N. J.; Blake, D. R.; Homeyer, C. R.; Brune, W. H.; Zhang, L.; Mao, J.; et al.
Abstract: One of the objectives of the Deep Convective Clouds and Chemistry (DC3) field experiment was to determine the scavenging of soluble trace gases by thunderstorms. We present an analysis of scavenging of hydrogen peroxide (H2 O2 ) and methyl hydrogen peroxide (CH3 OOH) from six DC3 cases that occurred in Oklahoma and northeast Colorado. Estimates of H2 O2 scavenging efficiencies are comparable to previous studies ranging from 79 to 97% with relative uncertainties of 5–25%. CH3 OOH scavenging efficiencies ranged from 12 to 84% with relative uncertainties of 18–558%. The wide range of CH3 OOH scavenging efficiencies is surprising, as previous studies suggested that CH3 OOH scavenging efficiencies would be <10%. Cloud chemistry model simulations of one DC3 storm produced CH3 OOH scavenging efficiencies of 26–61% depending on the ice retention factor of CH3 OOH during cloud drop freezing, suggesting ice physics impacts CH3 OOH scavenging. The highest CH3 OOH scavenging efficiencies occurred in two severe thunderstorms, but there is no obvious correlation between the CH3 OOH scavenging efficiency and the storm thermodynamic environment. We found a moderate correlation between the estimated entrainment rates and CH3 OOH scavenging efficiencies. Changes in gas‐phase chemistry due to lightning production of nitric oxide and aqueous‐phase chemistry have little effect on CH3 OOH scavenging efficiencies. To determine why CH3 OOH can be substantially removed from storms, future studies should examine effects of entrainment rate, retention of CH3 OOH in frozen cloud particles during drop freezing, and lightning‐NOx production. Key Points: Peroxide scavenging efficiencies derived from measurements Hydrogen peroxide is readily removed by storms Methyl hydrogen peroxide scavenging correlated with cloud physics and entrainment rate